Foucault, Psychology and the Analytics of Power - Hook, D. author. aut Link
XII, 301 p.
Keywords: This book introduces and applies Foucault's key concepts and procedures, specifically for a psychology readership. Drawing on recently published Collège de France lectures, it is useful to those concerned with Foucault's engagement with the 'psy-disciplines' and those interested in the practical application of Foucault's critical research methods.